Toxicity of Some Simple Plant Extracts Towards Three Species of Pheidole Ants (Hymenoptera: Formicidae) under Laboratory Conditions - Ali , Asmaa Saber; Ali , Mahmoud Fadl (Cutting Edge Research in Biology Vol. 4, 2023)
In recent years, the use of synthetic pesticides has raised concerns regarding human health. These undesirable aspects of pesticides have encouraged the study of alternative agents for pest control such as the use of plant-derived products with low toxicity, collectively described as biopesticides. As part of a preliminary study of some potential biopesticides, we have demonstrated the toxicity of extracts from nine familiar plants indigenous in Egypt against workers of three species of Pheidole ants under laboratory conditions. Crude extracts of the tubers of Allium sativum L., the seeds of Anethum graveolens L., Coriandrum sativum L., Trigonella foenum-graecum L and Nigella sativa L., flowers of Calendula officinalis L., and leaves of Mentha viridis L., Rosamarinus officinalis L and Eucalyptus citriodora Hook were tested in this way. Bioassays were performed on mature workers of three species of Pheidole ants; P. jordanica (Saulcy), P. laticeps (Mayr) and P. sinatica (Mayr) (Hymenoptera: Formicidae) also common in Egypt. All crude methanolic plant extracts were toxic to the three Pheidole species' workers. The crude methanolic extract of A. sativum was the most effective, as evidenced by the highest percentage mortality of ant workers, followed by extracts of T. foenum-graecum, and the crude extract of E. citriodora was the least active. The findings suggest that some of these plant extracts may be used as a source of secure substitutes for insecticides.